Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Tenaga Kerja Indonesia (Tki) Pada Balai Pelayanan Penempatan Perlindungan Tenaga Kerja Indonesia (Bp3tki) Di Bandara Achmad Yani Semarang - Ngesti, Tri; Hendratmoko, Christiawan (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
This research was carried out on House of Service Placement Protection for Indonesian Manpower (Balai Pelayanan Penempatan Perlindungan Tenaga Kerja Indonesia - BP3TKI) in Achmad Yani Airport, Semarang.  The aim of the study are:  (1) To know the influence of the dimensions of service quality (tangible, reliability, responsiveness, assurance, and emphaty) toward satisfaction of Indonesian Manpower.  (2) To know the dominant factor among the dimensions of service quality (tangible, reliability, responsiveness, assurance, and emphaty) that influence toward satisfaction of Indonesian Manpower. The hypothesis drawn are: (1) Presummed that there are influence of the dimensions of service quality (tangible, reliability, responsiveness, assurance, and emphaty) toward satisfaction of Indonesian Manpower. (2) Presummed that reliability has dominant influence toward satisfaction of  Indonesian Manpower. The population of this research is 100 TKI that received service from BP3TKI in Achmad Yani Airport, Smarang with  primary data. Technique of Analysis applied are validity test, reliability test, multiple linear regression, t-test , F- test and coefficient of determination. The results of this study are:  (1) There are simultaneous and significant influence of the dimensions of service quality (tangible, reliability, responsiveness, assurance, and emphaty) toward satisfaction of Indonesian Manpower.  (2) Reliability has dominant influence toward satisfaction of Indonesian Manpower that received service from BP3TKI in Achmad Yani Airport, Semarang.